If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 5x + 2 + x Reorder the terms: -10 = 2 + 5x + x Combine like terms: 5x + x = 6x -10 = 2 + 6x Solving -10 = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + -6x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + -6x = 2 + 0 -10 + -6x = 2 Add '10' to each side of the equation. -10 + 10 + -6x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -6x = 2 + 10 -6x = 2 + 10 Combine like terms: 2 + 10 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| 25899=1500x+5465 | | x-4(x-5)=40 | | 2ln(x)-ln(2x-1)=3 | | 2z-4=6 | | 0.04x+0.13(10000-x)= | | 8u=-1/3 | | 2(2x)+2(4)=40 | | 7u-2=4u+10 | | 2(2x)+2(2)=40 | | w+3.9=7.21 | | 130=95 | | -7+1=y-3y | | -24=5r+-8 | | 5(x+5)^1/2 | | x-1/2-7=x-5/3 | | (x+5)^5/2 | | (2/5d)-(1/9d) | | (6x+30)^3/2 | | 4x+5+3x+8=180 | | 21=-7/3w | | V+2v=15 | | -3(2x-2y)=-24 | | 1/3x+1/5y=-2/3 | | Q-17=17 | | 1/3+1/3(2x-15)=31/2 | | k^2=-3 | | 2(3x+y)=14 | | w-7/3=5/3 | | -4x(x-7)=40 | | x-7/2-1=x-5/3 | | 5y+8x=6(3.14) | | 6.3=b-1.5 |